What’s mathematics doing here? The role of mathematics in German Physics Olympiad tasks - Treiber, Eva; Neumann, Irene; Heinze, Aiso (Frontiers in Education, 2023)
Physics competitions target at motivating students for engaging in physics and at promoting students talented in physics. Physics competitions also aim at conveying a picture of physics as a scientific discipline, going beyond regular physics classes in school, and should thus also include a more intense mathematization of physics problems. Given that physics students often struggle with mathematics, mathematics in the competition may pose a challenge beyond the intended physics challenge. The present paper therefore presents an analysis of theoretical tasks employed in the German Physics Olympiad. Mathematical requirements were (1) identified by analyzing sample solutions and (2) compared to mathematics curricula. Then, (3) the solutions were categorized regarding whether the mathematics employed was used in a tool-like manner, a structuring manner, or both. Findings indicate that the first competition round typically includes rather basic mathematical requirements which are addressed in lower secondary mathematics education. In the higher rounds, more advanced mathematics is needed, which is only taught in the last years of high school, or not taught at all. The structural role of mathematics proved to be essential in the analyzed tasks. Beside the (intended) physics challenges, participants thus have to deal with mathematics they have not learned at school and have to apply mathematics in a different way than is often done at school when participating in the competition. As a consequence, unintended negative effects may occur, potentially counteracting the aim to promote students talented in physics. Implications for science education and future research are discussed.